Driving Innovation: A Case Study on Overcoming Challenges in the Automotive Industry’s Electric Vehicle Revolution of the 2010s - Thio Erika Stephanie; Alif Ikrami Bin Mutti (International Journal Labs, 2025)
The transition to electric vehicles (EVs) in the early 2010s marked a pivotal moment in the automotive industry, driven by environmental imperatives and technological advancement. Despite growing interest, the industry faced significant challenges including high battery costs, limited infrastructure, range anxiety, and consumer skepticism. This study aims to analyze how leading automakers such as Tesla, Nissan, and General Motors overcame these barriers to advance the EV revolution. Employing a qualitative case study approach, this research synthesizes secondary data from academic literature, industry reports, and historical documents to explore strategies related to innovation, policy, and business models. The findings show that Tesla’s investment in battery technology and Supercharger infrastructure, Nissan’s affordable EV offerings, and GM’s hybrid transition strategies collectively addressed both technical and market constraints. Government incentives further accelerated adoption. These efforts led to increased public trust, reduced EV production costs, and expanded charging networks, setting the foundation for EVs as a viable mainstream option. The study implies that the integration of innovation, regulatory support, and new business models is crucial to driving sustainable transformation. These insights offer a blueprint for future EV development and adoption, particularly in emerging markets.